PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL PEMBELAJARAN PADA MATA PELAJARAN MATEMATIKA - Nita Yunita; Santa .; Wawan Syahiril Anwar (Universitas Pakuan, 2020)
EFFECT OF THE APPLICATION OF THE DISCOVERY LEARNING MODEL ON LEARNING OUTCOMES IN MATHEMATICS SUBJECTSEffect of the Application of the Discovery Learning Model on Learning Outcomes in Mathematics Subjects in Class IV of Padarincang Elementary School, Cianjur Regency. This study aims to determine the effect of Discovery Learning models on the mathematics learning outcomes of statistical material. The experimental class N-Gain calculation (Discovery Learning group) is 56.99 while the control class N-Gain value (conventional group) is 43.81. So that the N-Gain value in the experimental class is greater than the control class. In the normality test with Lilliefors test both samples were normally distributed because the values of the two samples were smaller than Ltable. In the Discovery Learning group in Lcount (0.097) ≤ Ltable (0.147), in the conventional group obtained Lcount (0.107) ≤ Ltable (0.170). Then in the homogeneity test with Fisher's test the value of Fcount (1.39) ≤ Ftable (1.81) is obtained. Furthermore, the hypothesis test obtained a value of tcount of 3.222 greater than ttable of 1.99962, indicating that Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. Based on the results of the above research, it can be concluded that the Discovery Learning model has more influence compared to the conventional learning model towards the improvement of learning outcomes of fourth grade students of Padarincang State Elementary School in Cianjur district even semester 2018/2019 academic year.